AN APPROACH TO IMPROVING CUSTOMER ON-TIME DELIVERY AGAINST THE ORIGINAL PROMISE DATE - Ramachandran, G M; Neelakrishnan, S (The South African Journal of Industrial Engineering, 2017)
One of the main challenges that a low-volume high-variety (LVHV) product manufacturing industry faces is to improve customer on-time delivery (OTD) against the original promised date (OPD) in a make-to-order (MTO) situation. A systematic root-cause analysis is carried out in the LVHV industry to find the true root cause and eliminate it. This paper proposes a methodology that incorporates the lean thinking methodology, a lean live tracking (LLT) tool, and cross-functional team (CFT) approaches to improve OTD. These are tested using real-time data from an industrial valve manufacturing LVHV firm, resulting in an average OTD improvement from 30 percent to 90 percent in about eight months.